The safety and strength of a novel medial, partial non-threaded pedicle screw: a cadaveric and biomechanical investigation - Kwan, M.K.; Chan, C.Y.; Saw, L.B.; Shanmugam, R.; Lenke, L.G. (Lippincott, Williams & Wilkins, 2013)
STUDY DESIGN:: Cadaveric and biomechanical study. OBJECTIVE:: Assess the safety and pullout strength of medial, partial non-threaded thoracic pedicle screws compared to conventional screws. SUMMARY OF BACKGROUND DATA:: The perforation rate of pedicle screws has been reported as high as 41. Nerve injury and irritation can result from compression of malpositioned screw on neural structures. METHODS:: Ten fresh cadavers were studied. 5.0 mm and 6.0 mm screws were inserted from T1-T6 and T7-T12 respectively. Pedicle perforations and fractures were recorded upon screw insertion and final positioning (non-threaded portion facing medially) following a wide laminectomy. Pullout strength of novel and conventional screws were then tested using an Instron machine in an artificial bone substitute. RESULTS:: 240 thoracic pedicle screws were inserted. 88.8 (213 screws) were fully contained during screw insertion. There were 5.0 (12 screws) Grade 1 medial perforations and 6.2 (15 screws) Grade 1 lateral perforations during screw insertion. Upon final positioning, 93.8 (225 screws) were fully contained. All Grade 1 medial perforations, which occurred during insertion, were converted to Grade 0. No dural or nerve root injuries occurred. Pedicle split fractures were noted in 6.7 (16 screws). The use of medial, partial non-threaded screws reduced the overall perforation rate from 11.2 to 6.2. The mean pullout load for the 5 mm fully threaded screw vs. medial, partial non-threaded was 1419.3 N±106.1 (1275.8-1538.8 N) and 1336.6 N±44.2 (1293.0-1405.1 N) respectively, whereas 6 mm pullout load averaged 2126.0 N±134.8 (1986.3-2338.3 N) and 2036.5 N±210.0 (1818.4-2355.9 N). The difference was not statistically significant. CONCLUSION:: The use of medial, partial non-threaded pedicle screws reduced the medial perforation rate from 5.0 to 0; however, pullout strength was not significantly reduced. The use of this novel screw can potentially reduce the incidence of nerve injury or irritation following medial pedicle perforations.